Citra Perempuan dalam Novel Imperfect Karya Meira Anastasia dan Implikasinya terhadap Pembelajaran Bahasa Indonesia - Fustina, Siti Zulfah; Atmapratiwi, Heppy; Wiyanti, Endang (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
This study discusses Imperfect, a novel written by Meira Anastasia which tells about how the female figure is one of God's creatures who has privileges and also has a very noble position. The charm of female beauty is a gift that can make men fascinated. However, on the other hand, women are often referred to as a disaster, and are considered weak by some people. The image of women is an illustration that discoveries are often made by finding gender, but it is not uncommon for self-confidence to emerge. Therefore, it becomes an interesting thing to discuss by raising stories about the image of women. The purpose of this study was to determine the image of women in Imperfect, a novel written by Meira Anastasia and its implications in Indonesian language learning. This study used descriptive qualitative method. There are five studies on the image of women in Meira Anastasia's novel called Imperfect, namely Citra Pigura with 30 findings equal to 60%, Citra Pilar with 9 findings equal to 18%, Citra Peraduan with 4 findings equal to 9%, Citra Pinggan 1 finding equal to 2% and Citra Pergaulan 6 findings equal 12%. The dominant female image in Meira Anastasia's novel, Imperfect is the Citra Pigura and Citra Pilar.